A Conceptual Map of Academic Knowledge as an Image of the Condition of Universities - Kazimierz Przyszczypkowski (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
Introduction The article confronts the concept of academic knowledge, pointing to the main overlapping and interpenetrating areas of science. Research aim The aim of the article is to show the consequences of the fusion / clash of distant disciplines and the consequences of closing the narrative within one-dimensional paradigms. The aim of the text is also an attempt to look at the problems of the construction of academic knowledge. Evidence-based facts When building a knowledge-based society, it is worth taking the path of cognitive and scientific diversity that will allow us to maintain a balance in times that are uncertain for us. it is worth paying attention to diversity, which is the basic manifestation of the architecture of academic knowledge. This is its value and foundation. This differentiation also contains the message that non-scientific cognition (a) has a verbal form, lasts and has its infinity. Diversity and the resulting difference in defining specific problems in the architecture of academic knowledge should be treated equally, as it is not a difference in value. Summary A conceptual map of academic knowledge reflects the scientific and didactic condition of universities. The type and nature of these concepts indicate the scope of research and education. They are also an expression of the degree of autonomy of universities. The article is a proposal to build academic knowledge from the perspective of a generation, breaking the existing horizontal research perspective and opening up to a vertical perspective, simultaneously embracing various areas of science.